SOME COMPARATIVE OPINIONS REGARDING THE EVALUATION OF MAXIMUM STRESSES IN LONG FIBER REINFORCED COMPOSITES - RADU I. IATAN; NICOLETA SPOREA; CARMEN T. POPA; LUMINITA GEORGIANA ENACHESCU; COSMIN CIOCOIU; MELANIA CORLECIUC (MITUCA); ANDREEA - SILVIA NITU (Journal of Engineering Studies and Research)
This paper falls within the scope of current concerns for scientific and technical research, relating to technical structures made of composite materials, recognized for their mechanical, thermal and chemical or erosive resistance characteristics. In this case, the study is characterized by the analysis of the bearing capacity of some composites: a) with fibers applied along them, b) in a certain direction, c) in a direction perpendicular to the fibers, d) the stability of the structure along the fibers, e) in a direction perpendicular to the fibers or f) combined stress.